Toward elucidation of genetic and functional genetic mechanisms in corn host resistance to Aspergillus flavus infection and aflatoxin contamination - Shan, Xueyan; Williams, W. Paul (Frontiers in Microbiology, 2014)
Aflatoxins are carcinogenic mycotoxins produced by some species in the Aspergillus genus, such as A. flavus and A. parasiticus. Contamination of aflatoxins in corn profusely happens at pre-harvest stage when heat and drought field conditions favor A. flavus colonization. Commercial corn hybrids are generally susceptible to A. flavus infection. An ideal strategy for preventing aflatoxin contamination is through the enhancement of corn host resistance to Aspergillus infection and aflatoxin production. Constant efforts have been made by corn breeders to develop resistant corn genotypes. Significantly low levels of aflatoxin accumulation have been determined in certain resistant corn inbred lines. A number of reports of quantitative trait loci (QTLs) have provided compelling evidence supporting the quantitative trait genetic basis of corn host resistance to aflatoxin accumulation. Important findings have also been obtained from the investigation on candidate resistance genes through transcriptomics approach. Elucidation of molecular mechanisms will provide in-depth understanding of the host-pathogen interactions and hence facilitate the breeding of corn with resistance to A. falvus infection and aflatoxin accumulation.